2009
DOI: 10.1051/apido/2009069
|View full text |Cite
|
Sign up to set email alerts
|

Potential use of major royal jelly proteins (MRJPs) as molecular markers for royal jelly production in Africanized honeybee colonies

Abstract: -The present study determined the genetic variation at mrjps loci (mrjp3, mrjp5 and mrjp8) and evaluated the potential use of MRJPs as molecular markers for higher royal jelly production in Africanized honeybee colonies. The three analyzed loci produced a total of 17 alleles. This high allelic polymorphism indicated these loci could serve as genetic markers. The potential use of MRJPs as molecular markers for royal jelly production was evaluated by analyses of multiple linear regressions with EPD (expected pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
33
1
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(41 citation statements)
references
References 19 publications
6
33
1
1
Order By: Relevance
“…The mrjp5 locus had 6 alleles, with sizes of 570 bp (A), 590 bp (B), 610 bp (C), 620 bp (D), 680 bp (E), and 720 bp (F). In the present study, we detected different allelic compositions of mrjp3 and mrjp5 compared to those observed by Baitala et al (2010). For instance, the A and B alleles of mrjp3 that were previously detected by Baitala et al (2010) were not found in the queens that were analyzed in the current study (Table 2).…”
Section: Discussionsupporting
confidence: 40%
See 2 more Smart Citations
“…The mrjp5 locus had 6 alleles, with sizes of 570 bp (A), 590 bp (B), 610 bp (C), 620 bp (D), 680 bp (E), and 720 bp (F). In the present study, we detected different allelic compositions of mrjp3 and mrjp5 compared to those observed by Baitala et al (2010). For instance, the A and B alleles of mrjp3 that were previously detected by Baitala et al (2010) were not found in the queens that were analyzed in the current study (Table 2).…”
Section: Discussionsupporting
confidence: 40%
“…In the present study, we detected different allelic compositions of mrjp3 and mrjp5 compared to those observed by Baitala et al (2010). For instance, the A and B alleles of mrjp3 that were previously detected by Baitala et al (2010) were not found in the queens that were analyzed in the current study (Table 2). At the mrjp5 locus, alleles D, E, and F were detected in this study, together with four new alleles, called H (650 bp), I (750 bp), J (780 bp), and K (800 bp).…”
Section: Discussionsupporting
confidence: 40%
See 1 more Smart Citation
“…Selection for honey production was performed by evaluation of morphometric characteristics and emergence weight of queens and hygienic behavior by assessing the removal of dead brood within 24h by worker honeybees in colonies daughters of mother queens (Costa-Maia et al, 2011;Wielewski et al, 2012). The other group was composed of daughters of queens selected for royal jelly production using molecular markers for expressing the protein MRJP3 (Baitala et al, 2010) with a tendency to homozygosity for this locus (Parpinelli, Ruvolo-Takasusuki & Toledo, 2014). In the experiment II, besides these groups, we also evaluated a local group of queens, which were chosen at random in the apiary and were not subjected to any breeding process.…”
Section: Methodsmentioning
confidence: 99%
“…Nevertheless, the genetic material selected in breeding programs should be assessed under field conditions to validate the effectiveness of selection and adaptation of the lineages (Baitala et al, 2010) in other regions. This analysis also allows a better understanding of the genotype-environment interactions, since there are only a few studies on these interactions with bees (Faquinello et al, 2011).…”
Section: Introductionmentioning
confidence: 99%